Penerapan Sistem Manajemen Sumber Daya Perusahaan (ERP) Dalam Kinerja Manajemen Rantai Pasok (SCM) PT. Sas Majesty Wellness - Andrian Andrian; Rizni Aulia Qadri; Immanuel Zai; Jessyka Jessyka; Erni Astuti; Michelle Michelle (Journal Of Business, Finance, and Economics (JBFE), 2023)
The purpose of this research is to make every company run a diverse and competitive type of business, for a company to always grow and not lose competitiveness is to handle the company's operations well. The method that the writer uses to analyze the data in this study is data reduction, data presentation, and drawing conclusions. One important thing that needs to be considered is the inventory or supplies owned by the company. Grand Majesty SPA Company is a business engaged in massage and reflexology. There are various items needed to run the business and of course related to the company's inventory. This paper will discuss how the Grand Majesty SPA Company handles the company's inventory and the implementation of the ERP (Enterprise Resource Planning) system in the company's operations.